Effects of cycloheximide on the mortality of Atta sexdens leaf-cutting worker ants - Sousa, Kátia Kaelly Andrade [UNESP] (2018)
Leaf-cutting ants live symbiotically with a fungus that they cultivate on the plant leaves that they cut. The innumerous studies on the plant selection mechanism used by leaf-cutting ants show the researchers’ interest in this issue. Many classical studies propose that plants are selected according to the fungus garden nutritional needs and the absence of potentially harmful substances. This hypothesis is corroborated by behavioral experiments using cycloheximide (fungicide) with citric pulp or forage plants greatly accepted by leaf-cutting ants. According to this hypothesis, under the action of a fungicide, the fungus emits an allomone that informs worker ants that some food is inadequate to its growth. Although some authors state that the cycloheximide “fungicide” used is specific and non toxic to ants, our findings are distinct. In our study, various concentrations of cycloheximide were administered orally to leaf-cutting worker ants in a citric pulp paste diet. After the ingestion period, the ants were isolated and offered the symbiotic fungus for 21 days and the mortality rate was evaluated. As expected, the treatment with 0.01% cycloheximide showed a low mortality rate (8.86%). At 0.1%, the mortality rate was mild (27.85%), and treatment with 1% cycloheximide resulted in moderate mortality (45.57%). In contrast, the positive control with 0.1% sulfluramid showed a high mortality rate (91.14%). Therefore, we concluded that the ingestion of high concentrations of cycloheximide results in a moderate mortality rate in leaf-cutting worker ants.